1998
DOI: 10.2151/jmsj1965.76.6_983
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Life-Cycle of Atmospheric Blocking and the Analysis of Potential Vorticity Using a Simple Barotropic Model

Abstract: In this study, we conducted a series of numerical experiments to investigate atmospheric blocking, using a simple barotropic model that featured a wavemaker to excite synoptic disturbances. The model has a resolution equivalent to R20 and consists of only five physical processes: a wavemaker as baroclinic instability, topographic forcing, biharmonic diffusion, zonal surface stress, and Ekman pumping.Results of time integrations show that persistent dipole blockings appear one after another in the model, showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…A significant contribution of the upstream synoptic disturbances, as presented in this paper, is in agreement with the findings in the eddy straining mechanism (e.g., Shutts 1983;Chen and Juang 1992;Kimoto et al 1992;Nakamura et al 1997). The present study, based on waveletbased local spectral energetics, has extended the analysis in the previous studies that support the upscale energy cascade mechanism, equivalent to the eddy straining hypothesis (e.g., Saltzman 1959;Hansen and Sutera 1984;Kung and Baker 1986;Tanaka 1991). Figures 14 and 15 in local spectral energetics can be regarded as an extension of Fig.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…A significant contribution of the upstream synoptic disturbances, as presented in this paper, is in agreement with the findings in the eddy straining mechanism (e.g., Shutts 1983;Chen and Juang 1992;Kimoto et al 1992;Nakamura et al 1997). The present study, based on waveletbased local spectral energetics, has extended the analysis in the previous studies that support the upscale energy cascade mechanism, equivalent to the eddy straining hypothesis (e.g., Saltzman 1959;Hansen and Sutera 1984;Kung and Baker 1986;Tanaka 1991). Figures 14 and 15 in local spectral energetics can be regarded as an extension of Fig.…”
Section: Discussionsupporting
confidence: 74%
“…The traditional spectral energetics (e.g., Tanaka and Kung 1988;Hansen and Sutera 1984;Kung and Baker 1986) indicated that the eddy kinetic energy of the atmospheric blocking is primarily maintained by the upscale energy cascade from synoptic eddies through the wave-wave interaction, L n , during the formation. In this study, both the scales and longitudinal locations of the energy source region are clarified by applying the local spectral energetics analysis using the orthonormal wavelet expansion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations